The Role of Sabhara Two-Wheeled Patrol in Curanmor Prevention in Surabaya Police Jurisdiction - Reza Reyzaldy (Advances in Police Science Research Journal, 2021)
The number of reports of theft cases that occurred in the jurisdiction of the Surabaya Police in a period of four years (2017-2020) occupies the position of the highest crime case. This research was conducted to explain the role of the Satsabhara Turjawali Unit in maintaining security and safety through two-wheeled patrol activities as a form of prevention against the occurrence of theft and to explain the factors that influence the implementation of two-wheeled patrol activities of the Surabaya Police Satsabhara. Therefore, the author compiled a thesis with the title "The Role of the Two-Wheel Patrol of the Sabhara Unit in the Prevention of Theft in the Legal Territory of the Surabaya Police". POAC management theory (planning, organizing, actuating, controlling), 6M management element theory (man, money, materials, method, machine, market), role theory, and Perkabaharkam No. 1 of 2017 concerning patrols is used by the author in analyzing the data from the research that has been done. The research was carried out using a qualitative approach. In terms of sources of information, members of the Satsabhara Polrestabes Surabaya as the primary source and the author's secondary source involved the people of the City of Surabaya. The technique used by the author in collecting research data is by conducting interviews, observations, and document studies. In this study, the results obtained by the author are to provide a solution to the problem of high cases of theft through the role of the Turjawali Satsabhara Unit in carrying out two-wheeled patrol activities in order to prevent theft in the jurisdiction of Polrestabes Surabaya which is then applied with POAC management theory (planning, organizing, actuating, controlling). ), the theory of 6M management elements (man, money, materials, method, machine, market), role theory, and Perkabaharkam No. 1 of 2017 concerning patrols. Based on the results of research on the implementation of two-wheeled patrol activities by the Turjawali Satsabhara Unit, it has not been in line with expectations because the number of theft cases is still relatively high due to personnel carrying out patrols, a decrease in budget, facilities and infrastructure, and the method of carrying out patrols that have not reached outskirts. City of Surabaya.